Modeling Motorcyclists’ Involvement in Road Accidents: The Mediating Effect of Mindfulness - Amiruddin, Aidil Hanafi; Mohd Kassim, Muhammad Asyraf; Abdul Hanan, Suhaila; Abdullah, Muhammad Safizal (2022)
This study looks into the elements that relate mindfulness to road accidents, especially road fatalities among high-risk motorists. This study aims to analyze the literature on mindfulness to help shed light on high-risk road users, such as motorcyclists, on preventing themselves from being involved in road accidents through developing and promoting high-impact preventative countermeasures for long-term road safety. This study presents several significant characteristics relating to road user behavior that influence road accident occurrence. The findings revealed that motorcyclists’ behavioral factors such as anger, attitude, and sensation seeking are among the critical predictors to mindfulness and road accident involvement. This study intuitions have consequences for Malaysian transportation authorities and agencies in implementing high-impact remedies to minimize road accident proneness among high-risk road users in Malaysia